Optimal Load Frequency Control in Single Area Power System Using Pid Controller Based on Bacterial Foraging & Particle Swarm Optimization - Hong, Mee Song; Wan Ismail, Ibrahim; Nor Rul Hasma, Abdullah (Asian Research Publishing Network (ARPN), 2015)

(untitled)
In this paper, meta-heuristic optimization based on Particle Swarm (PSO) and Bacterial foraging (BFO) has been used to determine the optimal values of the proportional-integral-deviation (PID) controller for the load frequency control. Single area power system has been designed as a model network for Matlab-Simulink simulation. The comparison has been done between the conventional PI controller and PID controller tuned by Particle Swarm and Bacteria Foraging optimization technique. Based on time settling, transient and overshoot analysis, it can be concluded and profoundly proved that PID tuning by BFO technique is better than PSO technique and conventional PI controller.